Comparison of single-spin to double-spin platelet-rich plasma centrifugation methods in the treatment of androgenic alopecia: a systematic review and meta-analysis of randomized controlled trials - Laura Ghanem; Najwaa Kirmani; María Paula Palacios-Ortiz; Martin Cevallos-Cueva; Daniela Lucía Mendoza-Millán; Daniela Lucía Mendoza-Millán; Gabriel Victor Almeida Nascimento; Virginia Velasco-Tamariz (Frontiers in Medicine, 2025)
BackgroundAndrogenic alopecia (AGA) is the most common hair loss disease, caused by a combination of genetic factors and hormonal imbalances. Platelet-rich plasma (PRP) therapy has gained significant recognition in treating AGA, but optimal treatment protocol regarding centrifugation techniques has yet to reach a standardized consensus. We aim to conduct a systematic review and meta-analysis of randomized controlled trials (RCTs) to compare the efficacy of single-spin versus double-spin centrifugation protocols for PRP in patients with AGA.MethodsWe searched PubMed, Embase, and Cochrane for RCTs comparing single-spin to double-spin PRP in AGA patients. The primary endpoint was the final platelets count after centrifugation. Secondary endpoints included improvement in hair density, as well as terminal and vellus hair rate. Statistical analysis was performed using RStudio software. Heterogeneity was assessed with I2 statistics.ResultsWe included 90 participants with AGA from three RCTs. The pooled mean difference (MD) for platelets concentration was 66.14 in single-spin compared to double-spin PRP (95% CI: −372.96 to 505.25; p = 0.77; I2 = 83.5%). The MD for change in hair density was 4.10% in single versus double-spin (95% CI: −4.74 to 12.93; p = 0.36; I2 = 0%). Moreover, the MD for terminal and vellus hair after single-spin versus double-spin PRP was 1.16 (95% CI: −3.34 to 5.66; p = 0.61; I2 = 0%), and −3.59 (95% CI: −12.49 to 5.30; p = 0.45; I2 = 4.8%), respectively.ConclusionOur study suggests that single-spin PRP centrifugation is better in treating AGA patients compared to double-spin PRP.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025643296, identifier CRD42025643296.